2020
DOI: 10.1007/978-3-030-44769-4_4
|View full text |Cite
|
Sign up to set email alerts
|

Multiplayer Game Backends: A Comparison of Commodity Cloud-Based Approaches

Abstract: The development of resource-intensive complex distributed systems such as the backend side of Massively Multiplayer Online Games (MMOGs) has shifted towards cloud-based approaches in recent years. Despite this shift, researchers and developers have mostly utilized proprietary clouds to provide services for such applications -thus leaving the area of commodity clouds largely unexplored. The use of proprietary clouds is almost always applied at the Infrastructure-as-a-Service layer, thereby enforcing restriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Scalability and performance-In a previous work, we have demonstrated the limitations of several NoSQL data stores provided by popular public clouds such as Amazon's AWS, Google's Cloud Platform (GCP), and Microsoft's Azure [41]. Using a simplistic, tile-based game, we found that there are significant limitations on how many tiles of game state can be stored in a single object when using these data stores.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scalability and performance-In a previous work, we have demonstrated the limitations of several NoSQL data stores provided by popular public clouds such as Amazon's AWS, Google's Cloud Platform (GCP), and Microsoft's Azure [41]. Using a simplistic, tile-based game, we found that there are significant limitations on how many tiles of game state can be stored in a single object when using these data stores.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers and game developers have used a plethora of methods to implement and deploy their MMOGs on the cloud. Based on the results of previous studies [12,41] and insights from studying various games, we have developed a set of models, methods, and tools with which MMOG backends can be developed for and hosted on commodity cloud platforms. In this section, we describe our approach, presenting Athlos, a framework for developing scalable MMOG backends on commodity clouds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation